Efficient Isocyanide-less Isocyanide-Based Multicomponent Reactions - Neochoritis, Constantinos G. (Org Lett, 2015)
Isocyanides are the “Jekyll and Hyde” of organic chemistry allowing for extremely interesting transformations that are not only extremely odorous but also noxious. Therefore, an isocyanide-less isocyanide-based multicomponent reaction (IMCR) has been developed, and this protocol is expected to replace many of the old procedures in the future not only in IMCR but in other areas of organic chemistry as well. [Image: see text]